The Students’ Preference on Using Screen Text towards their Reading Comprehension - Trisilia Devana (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2019)
The objectives of this study was conducted to know the students’ preference on using screen text toward thier reading comprehension. In this case, finding out the information that can be used in teaching learning process toward improving the students’ reading comprehension is the focus of the educators. Moreover, the students’ familiarity reading the text by their mobile technology was as the source of information. The population of this study was students at English Education Study Program of Baturaja Univesity in academic year 2018/2019 and 36 students as sample. The research method was survey design, which to investigate the students’ response on the use of screen text relate to their reading comprehension. Questionaire was used in collecting the data, which was classified into four aspects: reading comprehension skills, retention and recall memory, motivation and psychology aspect. The data was analyzed the dominant percentage of each item. Based on the result, students were found to have higher positive preference of the reading by using screen text on the aspect of motivation. It could be concluded that reading a text on screen can give motivation for their reading skill and comprehension. Keywords : preference; screen text; reading comprehension